2017
DOI: 10.5121/ijsea.2017.8105
|View full text |Cite
|
Sign up to set email alerts
|

Culture Effect on Requirements Elicitation Practice in Developing Countries

Abstract: Requirement elicitation is a very important step into

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The result of the interview is a series of attribute/consequence/value chains that represent the interviewees' preferred product features and their reasoning for the preferences (Taylor-Cummings 1998). Sadig and Sahraoui (2017) also (without going into depth) looked at the requirements elicitation process in developing countries and argued that the national culture affects to a high degree the requirements elicitation techniques that are preferred and used.…”
Section: Cultural Aspects Of Requirements Elicitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of the interview is a series of attribute/consequence/value chains that represent the interviewees' preferred product features and their reasoning for the preferences (Taylor-Cummings 1998). Sadig and Sahraoui (2017) also (without going into depth) looked at the requirements elicitation process in developing countries and argued that the national culture affects to a high degree the requirements elicitation techniques that are preferred and used.…”
Section: Cultural Aspects Of Requirements Elicitationmentioning
confidence: 99%
“…As a result, even though contemporary synchronous and asynchronous communication tools may be used, communication needed for successful requirement elicitation is influenced negatively (Siakas et al 2021;Damian and Zowghi 2003). The challenges are intensified compared to developing software in a collocated environment (Aranda et al 2008;Benguria et al 2018;Mighetti and Hadad 2016;Sadig and Sahraoui 2017;Siakas et al 2016). Coordination and collaboration become particularly difficult in the context of GSE due to the need to coordinate many different stakeholders in a distributed multi-cultural setting.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly in the culture area, the study on national culture effect in [19] found 16 factors as. First, culture plays important role in choosing RE technique in Kuwait (*).…”
Section: The Findings From Literature Reviewmentioning
confidence: 99%
“…In this research, we have investigated several systematic literature reviews and systematic mapping studies regarding RE in ASD. Table 1 summarizes the challenges which affect the activities of RE in ASD, identified in 15 investigated papers numbered as follows: [3], [10], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24] and [25]. Table 1.…”
Section: Challenges That Affect Re In Asdmentioning
confidence: 99%
“…Customer involvement and interaction (Inadequate userdeveloper interaction, communication gaps) [3], [10], [14], [18], [19], [21], [22], [25 8 Difficulties with distributed teams [3], [13], [14], [15], [16], [20], [25] 9…”
Section: Id Description Of the Identified Challenges Sourcementioning
confidence: 99%